Genome-wide analyses of smoking behaviors in schizophrenia: findings from the Psychiatric Genomics Consortium - Peterson, Roseann E.; Bigdeli, Tim B.; Ripke, Stephan; Bacanu, Silviu-Alin; Gejman, Pablo V.; Levinson, Douglas F.; Li, Qingqin S.; Rujescu, Dan; Rietschel, Marcella; Weinberger, Daniel R.; Straub, Richard E.; Walters, James T. R.; et al. (Journal of psychiatric research, 2021)
While 17% of US adults use tobacco regularly, smoking rates among persons with schizophrenia are upwards of 60%. Research supports a shared etiological basis for smoking and schizophrenia, including findings from genome-wide association studies (GWAS). However, few studies have directly tested whether the same or distinct genetic variants also influence smoking behavior among schizophrenia cases. Using data from the Psychiatric Genomics Consortium (PGC) study of schizophrenia (35476 cases, 46839 controls), we estimated genetic correlations between these traits and tested whether polygenic risk scores (PRS) constructed from the results of smoking behaviors GWAS were associated with schizophrenia risk or smoking behaviors among schizophrenia cases. Results indicated significant genetic correlations of schizophrenia with smoking initiation (rg=0.159; P=5.05×10−10), cigarettes-smoked-per-day (rg=0.094; P=0.006), and age-of-onset of smoking (rg=0.10; P=0.009). Comparing smoking behaviors among schizophrenia cases to the general population, we observe positive genetic correlations for smoking initiation (rg=0.624, P=0.002) and cigarettes-smoked-per-day (rg=0.689, P=0.120). Similarly, TAG-based PRS for smoking initiation and cigarettes-smoked-per-day were significantly associated with smoking initiation (P=3.49×10−5) and cigarettes-smoked-per-day (P=0.007) among schizophrenia cases. We performed the first GWAS of smoking behavior among schizophrenia cases and identified a novel association with cigarettes-smoked-per-day upstream of the TMEM106B gene on chromosome 7p21.3 (rs148253479, P=3.18×10−8, n=3520). Results provide evidence of a partially shared genetic basis for schizophrenia and smoking behaviors. Additionally, genetic risk factors for smoking behaviors were largely shared across schizophrenia and non-schizophrenia populations. Future research should address mechanisms underlying these associations to aid both schizophrenia and smoking treatment and prevention efforts.